Пока волка нет: для чтения взрослыми детям / пер. с фр. О. Ярикова - Баттю Эрик (Clever, 2011)
Экземпляры: ДБ (20120426) / Инвентарный номер: 40729zzzzz / Цена: 225.00 / Сис.шифр: 84(4Фра) / Авт.знак: Б 28 / ГРНТИ: 17.82.93 / ББК: 84(4Фра)